The Atlas Milestone: Celebrating virtual memory, which has made such a difference in how we approach programming, memory management, and secure computing. - Denning, Peter; Ibbett, Roland (Communications of the ACM, 2022)
This article reviews the development of virtual memory and its impact on the computing industry. Topics include the discovery of virtual memory including the Atlas architecture, operating system, and programming language that led to it as well as its impact on overall computer memory, multi-programming and secure computing.